Brain control among middle school principals - نادية عريبي فدعم أ . م . د. نعيمة خلف زيدان (الرياضة المعاصرة)
The objective of the research is to: - Prepare the scale (adaptation to the Iraqi environment) Brain control of (Connell, 2005) and to identify the type of brain control in the principals of junior high schools. The researchers used the descriptive approach. The research sample consisted of principals (principals and managers) in the first Rusafa / Baghdad governorate for the academic year 2018/2019 (20 managers and directors). The researchers prepared the Connell (2005) The majority of managers (principals and principals) in the middle schools had left-brain control, and the proportion of female managers with right and left brain control was more than Percentage of managers with the same Control. The researchers concluded that the number of managers with integrated brain control was higher than the number of female managers with integrated brain control